Students' Mathematical Problem Solving Ability in Elementary School: Kemapuan Pemecahan Masalah Matematis Siswa di Sekolah Dasar - Dwi Siska Putri Utami; Enik Setiyawati (Academia Open, 2022)
The purpose of this study was to describe the results of a literature study on mathematical problem solving abilities in elementary schools. This research uses a qualitative descriptive study approach with the type of literature study research. This research is a literature study or library research that describes descriptively the mathematical problem solving abilities of students in elementary schools. The subjects of this study were elementary school students related to their ability to solve mathematical problems. The data sources for this research are secondary data obtained from scientific journals or articles related to the problems discussed. The data will be analyzed using descriptive analysis techniques. The results showed that students' mathematical problem solving abilities still tended to be low. Students have not achieved all of the problem solving indicators. The factors that influence students' mathematical problem solving abilities include prior knowledge, appreciation of mathematics, logical mathematical intelligence, experience, motivation, skills, self-confidence and teachers. Highlights: Students' mathematical problem solving abilities are low. Not all problem solving indicators are achieved. Factors influencing problem solving include prior knowledge, motivation, and teachers. Keywords: Mathematical problem solving abilities, Elementary schools, Literature study, Descriptive analysis, Factors influencing problem solving.